The effect of climate change anxiety on social work students in Turkey - Dogan, Huseyin; Buz, Sema (Sage Publications Ltd, 2024)
This study aims to explore the impact of climate change anxiety on various aspects of social work and examine the relationship between anxiety and socio-demographic variables. The study's participants comprised students enrolled in social work education programs in Turkey. The results suggest that students who are highly anxious about climate change express anxiety regarding various problem areas within social work. The study suggests that anxieties about climate change can potentially lead to anxiety within social work domains, thus exerting a negative impact on social work policy and practices.
Keywords: Climate change anxiety; ecological social work; migration; poverty; social inequalities; vulnerable groups